The Sound of Batteries: An Operando Acoustic Emission Study of the LiNiO2 Cathode in Li–Ion Cells. Issue 10 (14th July 2020) - Schweidler, Simon; Bianchini, Matteo; Hartmann, Pascal; Brezesinski, Torsten; Janek, Jürgen
Abstract: The development of advanced Li‐ion batteries relies on the implementation of high‐capacity Ni‐rich layered oxide cathode materials, such as NCM and NCA, among others. However, fast performance decay because of intrinsic chemical and structural instabilities hampers their practical application. Hence, thoroughly understanding degradation processes is crucial to overcome current limitations. To monitor instabilities of electrode materials under realistic operating conditions, the application of nondestructive operando techniques is required. While structural changes of crystalline phases can be studied by X‐ray diffraction, microstructural changes (e. g., particle fracture) cannot be easily accessed in situ and are therefore mostly investigated ex situ . Here, we use acoustic emission (AE) measurements to probe a potential next‐generation cathode material in real‐time. Specifically, we focus on LiNiO2 (LNO) and demonstrate that AE events in different frequency ranges can be correlated with the formation of the cathode solid‐electrolyte interphase and the mechanical degradation during electrochemical cycling. Abstract : Battery beats : Acoustic emission is a versatile and nondestructive method for operando monitoring degradation of battery materials. Here, it is applied to probe in real‐time the cathode active material LiNiO2 (LNO) upon electrochemical cycling in lithium‐ion cells.